Outcomes and management of delayed complication after severe blunt liver injury - Masaaki Kagoura; Kazuteru Monden; Hiroshi Sadamori; Masayoshi Hioki; Satoshi Ohno; Norihisa Takakura (BMC Surgery, 2022)
Abstract Background The treatment of delayed complications after liver trauma such as bile leakage (BL) and hepatic artery pseudoaneurysms (HAPs) is difficult. The purpose of this study is to investigate the outcomes and management of post-traumatic BL and HAPs. Methods We retrospectively evaluated patients diagnosed with blunt liver injury, graded by the American Association for the Surgery of Trauma Liver Injury Scale, who were admitted to our hospital between April 2010 and December 2019. Patient characteristics and treatments were analyzed. Results A total of 176 patients with blunt liver injury were evaluated. Patients were diagnosed with grade I–II liver injury (n = 127) and with grade III-V injury (n = 49). BL was not observed in patients with grade I–II injury. Eight patients with grade III-V injury developed BL: surgical intervention was not needed for six patients with peripheral bile duct injury, but hepaticojejunostomy was needed for two patients with central bile duct injury. Out of 10 patients with HAPs, only three with grade I–II injury and one with grade III–V were treated conservatively; the rest six with grade III-V injury required transcatheter arterial embolization (TAE). All pseudoaneurysms disappeared. Conclusions Severe blunt liver injury causing peripheral bile duct injury can be treated conservatively. In contrast, the central bile duct injury requires surgical treatment. HAPs with grade I–II injury might disappear spontaneously. HAPs with grade III–V injury should be considered TAE.